A phase-field microscale enhancement for macro models of capillary-driven contact point dynamics. (September 2017) - Kronbichler, Martin; Kreiss, Gunilla
We present a method to determine the relation between contact point velocity and contact angle, which can be used as a boundary condition for simulating immiscible and incompressible fluids in contact with solids. The relation is determined from a micro model based on the phase field method. The micro model performs a steady-state computation in a box around the contact point, with far field data given by the macroscale wall contact angle. The size of the micro box is chosen such that physical diffusive processes around the contact point are fully represented. The contact point velocity is shown to converge with respect to the size of the micro box. The angle–velocity relation determined by the micro model is verified on a parameter setting that can be represented by a full phase field simulation.